Acupressure versus parecoxib sodium in acute renal colic: A prospective cohort study - Chen, Chiwei; Zhang, Zhenpeng; Lin, Mandi; Wang, Zhigang; Liu, Hao; Meng, Hao; Wang, Jun; Chen, Ming; Xiang, Songtao; Qiu, Yunqiao; Liu, Hong (Frontiers in Medicine, 2023)
Here provides a complementary treatment, acupressure at the Qiu acupoint, a novel acupoint, which potentially alleviates renal colic. 90 patients were included in this study. Acupressure-group patients (n=46) were administered acupressure at the Qiu acupoint following a preset protocol. Parecoxib sodium-group patients (n=44) were administered parecoxib sodium (40 mg) (via the direct intravenous route). The visual analog scale (VAS) was used to evaluate pain intensity at baseline and at 1, 5, 10, 20, 30, and 120 min after initiating the intervention. Linear mixed effects model was performed to detect the rate of decrease of VAS per time and their covariant effect on the efficacy of acupressure. No significant statistical differences in baseline data and VAS scores were observed. The acupressure group obtained lower VAS scores at the 1st, 5th, 10th, and 20th minute than the parecoxib sodium group after initiating the intervention (mean: 4.33 vs. 7.61, mean difference (MD): 3.29, 95%CI: 0.23, 2.84; mean: 2.65 vs. 7.61, MD: 4.96, 95%CI: 4.44, 5.49; mean: 1.63 vs. 6.59, MD: 4.96, 95%CI: 4.48, 5.44; mean: 1.26 vs. 3.64 MD: 2.38, 95%CI: 1.87, 2.88; P<0.05). The markedly effective rate was similar between the two groups. The linear mixed effects model demonstrated that acupressure at the Qiu point was significantly faster than parecoxib sodium in decreasing VAS scores with an estimate of -2.05 (95%CI: -2.51, -1.59, p= 0.000), especially within 10 minutes with an estimate of 0.18 (95%CI: 0.12, 0.25, p= 0.000). Trial registration: Chinese clinical trial registry, ChiCTR2100047168. Registered 9 June 2021,http://www.chictr.org.cn/ ChiCTR2100047168